The general framework of the EU environmental policy and harmonization of the policy and legislation of the Republic Serbia - Todić, Dragoljub (Hotel and Tourism Management, 2013)
The paper provides a summary of the basic elements of the European Union (EU) policy in the environmental field. In particular, it highlights the issue of EU competences for work in the environmental field, objectives and principles of the EU in the field of the environment, the basis of its strategic orientation in the field of environment and structure of the regulations. Given the fact that the Republic of Serbia (RS), for nearly a decade, works on harmonizing its policies and regulations with the policies and regulations of the European Union, in the second part of the paper it is given an overview of the legal basis embodied in the Stabilisation and Association Agreement. In addition, the other elements of importance for the assessment of the achieved level of harmonization of national legislation of the RS with EU regulations are also emphasized.